2015
DOI: 10.1021/acs.biomac.5b00817
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties and Electrospinnability of High-Amylose Starch in Formic Acid

Abstract: Starch derivatives, such as starch-esters, are commonly used as alternatives to pure starch due to their enhanced mechanical properties. However, simple and efficient processing routes are still being sought out. In the present article, we report on a straightforward method for electrospinning high-amylose starch-formate nanofibers from 17 wt % aqueous formic acid (FA) dispersions. The diameter of the electrospun starch-formate fibers ranged from 80 to 300 nm. The electrospinnability window between starch gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 59 publications
5
39
1
Order By: Relevance
“…Fibers with 8 wt % PVA were thinner and more uniform (175 ± 27 nm; Figure 4c) than those prepared with higher PVA contents (e.g., 262 ± 39 nm obtained at 10 wt % PVA; Figure 4d). Consistent with other electrospinning studies [39,40], our best mat showed simultaneously high TS and EB. This could relate with the mechanism of load transfer during mechanical tests [12]; under tension, the non-aligned PVA fibers will rearrange due to the load exerted on the fiber network (and not on individual fibers as in the case of aligned fibrous mats) which will cause the fibrous mats to elongate more or less depending on the number of fiber ends the tensile grips will grab.…”
Section: Resultssupporting
confidence: 92%
“…Fibers with 8 wt % PVA were thinner and more uniform (175 ± 27 nm; Figure 4c) than those prepared with higher PVA contents (e.g., 262 ± 39 nm obtained at 10 wt % PVA; Figure 4d). Consistent with other electrospinning studies [39,40], our best mat showed simultaneously high TS and EB. This could relate with the mechanism of load transfer during mechanical tests [12]; under tension, the non-aligned PVA fibers will rearrange due to the load exerted on the fiber network (and not on individual fibers as in the case of aligned fibrous mats) which will cause the fibrous mats to elongate more or less depending on the number of fiber ends the tensile grips will grab.…”
Section: Resultssupporting
confidence: 92%
“…A small displacement in the bands from soluble potato starch (2931, 1647, 1338, 1076, and 991 cm −1 ) was observed when compared with those of ultrafine fibers in solutions with different aging times (Table ). During the chemical gelatinization of the starch and formic acid solutions, reorganization occurs, and starch macromolecules tend to aggregate as a function of solution aging times . This observation suggests interactions between the hydrogen bounds of starch and the solvent, and may be the reason for the small displacement in the bands observed when the same fiber‐forming solution is compared at different aging times.…”
Section: Resultsmentioning
confidence: 99%
“…However, in these cases, starch is not the principal polymer in the resulting fiber. Thus, to the best of our knowledge, there are no studies on the production of fibers using starch with normal amylose content (for potato starch, the normal amylose content ranges from 25% to 30%), and existing studies are focused on fibers produced from starch in combination with other polymers or with high amylose content …”
Section: Introductionmentioning
confidence: 99%
“…While starch gelatinization is expected to occur below 100 °C (heating temperature of our starch dispersions) the transition from an helical to random coil conformation of starch molecules, which favors fiber formation, will only occur ~160 °C [12]. For this reason, native starch fibers have only been obtained by electro-wet-spinning technology from DMSO solutions [10,11,12,13] while electrospinning has only been possible using starch derivatives [15,34] or starch blends with synthetic polymers [29,30].…”
Section: Correlation Between Rheology and Fiber Formationmentioning
confidence: 99%
“…Pure starch fibers in turn, could only be obtained from Dimethyl Sulfoxide (DMSO) solutions using electro-wetspinning technology due to the non-volatile nature of the organic solvent [12,13]. Starch derivatives have also been electrospun from formic acid solutions [15,34] while composite fibers have been produced from blends of starch with non-food grade polymers such as polyvinyl alcohol [29] and polylactic acid [30]. …”
mentioning
confidence: 99%